Análise morfométrica da pele fetal ao nascimento como marcador da cronologia gestacional - Ingrid Michelle fonseca de Souza (2020)
Introduction: Functional and structural maturation of the skin is a potential marker for dating the chronology of pregnancy. It is the result of a dynamic process, which begins during embryogenesis and ends in the first year of life. It is already known that there is an association between the development of the epidermal protective barrier and neonatal survival. Despite the importance of morphometric analysis of the skin for clinical applications in neonatology, there are few studies regarding the chronological evolution of these measures during pregnancy, mainly due to the limitations in obtaining the specimen. Objective: To evaluate the relationship between the thickness and the amount of fibrous connective tissue, areas of the newborn's skin glands with the pregnancy chronology. Methodology: cross-sectional observational study, in which skin thickness measurements were obtained by means of biopsies in 35 dead bodies with gestational age between 20 and 42 gestational weeks. Inclusion criteria were: existence of early obstetric ultrasound in pregnancy before 14 weeks of gestational age (GA) and a maximum interval of 48 hours between death and skin sample biopsy. The biopsied regions were: the skin on the hand, sole of the foot and abdômen. The dimensions of the skin layers were measured with the support of the KS300 image analysis software. The histological slides were stained by Gomori's trichrome. The statistical analysis determined the dimensions of the skin layers and their variability, comparison between regions of the body and calculated the correlation between the morphometric characteristics of the skin and the GA. Results: The thickness of the skin was similar on the hand and on the sole of the foot: stratum corneum (p = 0.707), epidermis (p = 0.618) and dermis (0.977). However, the skin was thinner on 19 19 the abdomen when compared to the hand (p = 0.002; p <0.001; p = 0.002) and sole of the foot (p = 0.002; p <0.001; p = 0.002), respectively for each layer. The best correlation between GI and skin histomorphometric characteristics was with the epidermal layer on the palm (r = 0.867, p <0.001). The amount of fibrous connective tissue showed a weak correlation with GA: r = 0.518 p = 0.014 in the hand, r = 0.538 p = 0.071 in the abdomen r = -0.266 p = 0.189 for the sole. A strong correlation was observed between the thickness of the epidermis, the dermis and the area of the sebaceous glands in the skin of the abdomen with GA (r = 0.99, p <0.001). Conclusion: The study signals a new opportunity to correlate gestational age with the layers of neonatal skin at birth. And this relationship could be an important tool to assist in the development of new technologies to determine GA with high accuracy, revealing the moment of death in the gestational cycle, especially when the chronology of pregnancy is unknown.